Genetic Incorporation of the Favorable Alleles for Three Genes Associated With Spikelet Development in Wheat - Zhang, Xiaojun; Qiao, Linyi; Li, Xin; Yang, Zujun; Liu, Cheng; Guo, Huijuan; Zheng, Jun; Zhang, Shuwei; Chang, Lifang; Chen, Fang; Jia, Juqing; Yan, Liuling; et al. (Frontiers in Plant Science, 2022)
The number of spikelets per spike is an important trait that directly affects grain yield in wheat. Three quantitative trait loci (QTLs) associated with spikelet nodes per spike (SNS) were mapped in a population of recombinant inbred lines generated from a cross between two advanced breeding lines of winter wheat based on the phenotypic variation evaluated over six locations/years. Two of the three QTLs are QSns.sxau-2A at the WHEATFRIZZY PANICLE (WFZP) loci and QSns.sxau-7A at the WHEAT ORTHOLOG OF APO1(WAPO1) loci. The WFZP-A1ballele with a 14-bp deletion at QSns.sxau-2A was associated with increased spikelets per spike. WAPO-A1e, as a novel allele at WAPO1, were regulated at the transcript level that was associated with the SNS trait. The third SNS QTL, QSns.sxau-7D on chromosome 7D, was not associated with homoeologous WAPO-D1 or any other genes known to regulate SNS. The favourable alleles for each of WZFP-A1, WAPO-A1 and QSns.sxau-7D are identified and incorporated to increase up to 3.4 spikelets per spike in the RIL lines. Molecular markers for the alleles were developed. This study has advanced our understanding of the genetic basis of natural variation in spikelet development in wheat.